(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2022)
Human resources has an important role to running a government institutions. The purpose of this research was to analyze and explain the effect of organizational culture, organizational justice and job satisfaction toward organizational citizenship behavior (OCB) with organizational commitment as intervening variables in the Education Office of Banyumas District. This research is a quantitative using a questionnaire of 104 respondents to government employees of the Education Office of Banyumas District. The sampling technique used purposive sampling method. Data analysis used multiple linear regression. The result of this study shows that organizational culture and organizational justice have no effect on organizational commitment, but job satisfaction has a positive and significant effect on organizational commitment. Organizational culture and job satisfaction have a positive and significant effect on OCB, but organizational justice and organizational commitment have no effect on OCB. Organizational commitment variables can not mediate of organizational culture, organizational justice and job satisfaction on OCB. Keywords: Anteseden OCB, Organizational Commitment, Intervening